1-Palmitoyl-2-Linoleoyl-3-Acetyl-rac-Glycerol (PLAG) Mitigates Monosodium Urate (MSU)-Induced Acute Gouty Inflammation in BALB/c Mice - Shin, Su-Hyun; Jeong, Jinseon; Kim, Joo Heon; Sohn, Ki-Young; Yoon, Sun Young; Kim, Jae Wha (Frontiers in Immunology, 2020)
Acute gouty arthritis is an auto-inflammatory disease caused by the deposition of monosodium urate (MSU) crystals in joints or tissues. Excessive neutrophil recruitment into gouty lesions is a general clinical sign and induces a pain phenotype. Attenuation of successive periods of neutrophil infiltration might be a beneficial approach to achieve therapeutic efficacy. In this study, the activity of 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) in attenuation of excess neutrophil infiltration was assessed in gout-induced lesions of BALB/c mice. Neutrophil infiltration in MSU-induced gouty lesions was analyzed using immunohistochemical staining. ELISA and RT-PCR were used to measure attenuation of expression of the major neutrophil chemoattractant, CXC motif chemokine ligand 8 (CXCL8), in a PLAG-treated animal model and in cells in vitro. The animal model revealed massive increased neutrophil infiltration in the MSU-induced gouty lesions, but the PLAG-treated mice had significantly reduced neutrophil numbers in these lesions. The results also indicated that the MSU crystals stimulated a damage-associated molecular pattern that was recognized by the P2Y6 purinergic receptor. This MSU-stimulated P2Y6 receptor was destined to intracellular trafficking. During intracellular endosomal trafficking of the receptor, endosome-dependent signaling provided expression of CXCL8 chemokines for neutrophil recruitment. PLAG accelerated initiation of the intracellular trafficking of the P2Y6 receptor and returning the receptor to the membrane. This process shortened the intracellular retention time of the receptor anchoring endosome and subsequently attenuated endosome-dependent signaling for CXCL8 expression. These study results suggested that PLAG could be used for resolution of acute inflammation induced in gout lesions.